When Puerto Rico Talked to the World: Pioneering Dubbing in the Caribbean. Issue 1 (2nd January 2021) - Fuentes-Luque, Adrián
Abstract : This article presents a historical overview of audiovisual translation (AVT) in Puerto Rico, as a pioneering country in audiovisual translation in the Caribbean, which became a true dubbing power in the Spanish-speaking world from 1958 to the late 1970s. Special emphasis is placed on the factors that influenced the establishment of AVT modes in the region. The language model (i.e., the Spanish-language variety) used in audiovisual translation in different Latin American countries, and the use and influence of the so-called 'neutral Spanish' on the implementation of the different AVT modes in the various Spanish-speaking countries will be discussed. Also, the work process and conditions of audiovisual translators in Puerto Rico are described.